Clinical value of heparin-binding protein in adult bacterial intracranial infection - Linsai Guan; Feiyao Wang; Jingni Chen; Yanxin Xu; Weixing Zhang; Jianping Zhu (Frontiers in Cellular and Infection Microbiology)
BackgroundThe accurate and sensitive diagnosis of intracranial infection continues to pose a critical challenge. This study aimed to probe into the clinical value of heparin binding protein (HBP) in bacterial intracranial infection.MethodsPatients suspected of having bacterial intracranial infection and admitted to Shanghai General Hospital from November 2021 to November 2023 were selected as study subjects and divided into an infected group and a non-infected group. The receiver operating characteristic (ROC) curve was constructed to compare the diagnostic accuracy of HBP, procalcitonin (PCT), and C-reactive protein (CRP), as well as their value in differentiating Gram-positive bacteria and Gram-negative bacterial infections.ResultsAccording to the results of bacterial identification, the infected groups were divided into a Gram-negative bacteria group (n = 142) and a Gram-positive bacteria group (n = 128), while the non-infected group comprised 120 patients after neurosurgery involving dura opening. Statistically significant differences were observed in the levels of HBP, PCT, and CRP between the infected group and the non-infected group (all p< 0.05). Receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of HBP was 0.935, and the AUCs of PCT and CRP were 0.931 and 0.863, respectively. In the comparison of HBP, PCT, and CRP levels in the Gram-negative bacteria and Gram-positive bacteria groups, the AUCs were 0.816, 0.602, and 0.591, respectively. When the cutoff value of HBP was 72.34 ng/mL, its specificity reached 96.1% and its sensitivity was 57.8%. When PCT and CRP levels were less than 1.67 ng/mL and 23.12 ng/mL, respectively, both the sensitivity (52.3%, 53.1%) and specificity (66.9%, 59.9%) were relatively low.ConclusionHBP, PCT, and CRP can be employed as diagnostic indicators for bacterial intracranial infection. HBP (>72.34 ng/mL) can act as an important index for the diagnosis of Gram-negative bacteria in patients with intracranial infection.